Occurrence and detection of extended-spectrum beta-lactamases in members of the family Enterobacteriaceae at a veterans medical center: seek and you may find. - Coudron, P E (1997)
A total of 907 consecutive isolates of members of the family Enterobacteriaceae recovered during a 20-week period were tested for production of extended-spectrum beta-lactamases (ESBLs) by the double-disk (DD) potentiation method. Of 84 DD-positive isolates, 83 (9.2%) produced ESBLs based on isoelectric focusing. SHV-derived ESBLs and several TEM-derived ESBLs were present in nine species, including the first isolate of Citrobacter koserii and Morganella morganii known to harbor an SHV-derived ESBL. Results of testing 58 nonrepeat isolates for ESBL production by several recommended methods were as follows (percent detected in parentheses): DD method with aztreonam (95), ceftazidime (79), ceftriaxone (88), or cefpodoxime (90); broth microdilution method with ceftazidime (86) or cefotaxime (91) alone or in combination with clavulanate; and the standard disk diffusion method with new breakpoints and standard concentrations of aztreonam (78), ceftazidime (79), ceftriaxone (83), or cefpodoxime (98) or a novel concentration (5 microg) of ceftazidime (88). In three instances during an extended part of the study, an ESBL-producing isolate and a non-ESBL-producing isolate of the same species were recovered from a single blood culture bottle. These data indicate that ESBLs occur in several species of Enterobacteriaceae and at a relatively high incidence at our institution and that the standard disk diffusion method with cefpodoxime and the DD method with several beta-lactams are practical and cost-effective methods for detecting ESBL-producing isolates of Enterobacteriaceae.